Improving Mathematical Connection Skills through Eliciting Activities in 8th-Grade Students at SMP Negeri 1 Bangkinang Kota - Ervinasari, Bunga; Arnawa, I Made (FKIP Universitas Lampung, 2024)
This research aims to examine the influence of the Eliciting Activities learning model on student’s mathematical connection skills. It is a quasi-experimental study using a nonequivalent control group design, with the population being eighth grade students at SMP Negeri Bangkinang Kota. The sample consists of two classes selected through purposive sampling: class VIII F as the experimental class of two classes selected through purposive sampling: class VIII F as the experimental class using the Eliciting Activities model and class VIII E as the control class using conventional teaching methods. Data collection techniques involved tests and observations. Hypothesis testing was conducted using a paired t-test with a significance level of < 0.025. Prior to this, prerequisite tests were performed, including a normaity test using the Kolmogrorov-Smirnov test and a homogeneity test using Levene’s test. Based on the analysis results, the paired t-test yielded a significance value (2-tailed) of 0.000 < 0.025, indicating that the null hypothesis (H0) is rejected. Therefore, it can be concluded that using the Eliciting Activities learning model significantly affects the mathematical connection skills of eighth-grade students at SMP Negeri 1 Bangkinang Kota. Keywords: model eliciting activities (MEA), mathematical connection skills, learning model. DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1799-1808